Resposta :
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo a passo:
[tex]\sf{n! + \dfrac{48}{n!} = 26}[/tex]
[tex]\sf{(n!)^2 - 26(n!) + 48 = 0}[/tex]
[tex]\mathsf{y = n!}[/tex]
[tex]\sf{y^2 - 26y + 48 = 0}[/tex]
[tex]\sf{y^2 - 26y + 48 + 121 = 0 + 121}[/tex]
[tex]\sf{y^2 - 26y + 169 = 121}[/tex]
[tex]\sf{(y - 13)^2 = 121}[/tex]
[tex]\sf{y - 13 = \pm\:\sqrt{121}}[/tex]
[tex]\sf{y - 13 = \pm\:11}[/tex]
[tex]\sf{y' = 11 + 13 = 24}[/tex]
[tex]\sf{y'' = -11 + 13 = 2}[/tex]
[tex]\mathsf{n! = 24 \Leftrightarrow n = 4}[/tex]
[tex]\mathsf{n! = 2 \Leftrightarrow n = 2}[/tex]
[tex]\boxed{\boxed{\mathsf{S = \{4;2\}}}}[/tex]